Cultivo da alga marinha vermelha Solieria filiformis (Kützing) P.W. Gabrielson: textura de géis aquosos e lácteos - Lima, Ticiana de Brito (2012)
The red seaweed Solieria filiformis, abundant in Ceará, biossintetiza, among other polysaccharides, phycoloide called carrageenan of great commercial importance due to its properties thickeners, stabilizers and gelling agents. In Brazil, exotic species of marine algae are being grown on a commercial scale in order to meet the demand of industrial phycoloide. The aim of this study was to analyze the texture of aqueous gels made with milk and carrageenan extracted from seaweed S. filiformis, cultivated in Ceará through sporulation natural technique, in order to establish a comparison between these gels and those prepared with commercial carrageenans (iota and kappa carrageenan). The algae were grown through sporulation natural, where monthly PVC structures (25 mm) in size 25 x 44 cm, each containing a single nylon cord (10 mm) of 23 m length were kept at depths of 1 and 2 m over a period of nine months. For extraction of carrageenan were collected at both depths seaweed samples S. filiformis backstage with higher and lower biomass, some for the rainy season (January and April) and dry (October and November). Initially, the algae were dried, crushed in electric grinder and subjected to aqueous extraction (1.5% m / v), stirring every 20 minutes in a water bath at 90 °C for 4 h. The homogenates were filtered through nylon cloth, the waste discarded. The filtrates were subjected to filtration on a vacuum funnel sintered plate, and carrageenans obtained were frozen, lyophilized and weighed. The highest yields were obtained from carrageenan seaweed collected from the scenes that have accumulated during the dry spores (35.6% - November 2M to 45.3% - October 1M), while the algae that accumulated during the rainy season had the lowest incomes (29 6% - April 1M to 33.8% - April 2M). In contrast, levels of total sugars ranged between 37.6 and 50.5% and the content of carrageenan sulfate ranged from 21.6 to 33.3% according to the levels already checked to carrageenans of the iota type. The texture of aqueous gels in the presence of CaCl2 and 0.1% milk prepared with carrageenan S. filiformis and commercial concentrations of 0.5 and 1.5%, were analyzed for firmness, adhesiveness, cohesiveness, springiness, gumminess and chewiness. All samples with carrageenan derived from S. filiformis backstage obtained values of firmness, gumminess and chewiness than those found for ι-carrageenan commercial. Backstage November had the highest values in the parameter of firmness for aqueous gels and compared to ι-carrageenan commercial dairy. Adhesiveness, elasticity and cohesiveness showed values close to those found for ι-carrageenan commercial. The results for firmness and chewiness of κ-carrageenan were superior when compared to commercial car ι-carrageenan and S. filiformis. The gels formulated with milk obtained results strongly higher than those formulated with a solution of calcium chloride 0.1% due to interactions between the proteins and the milk carrageenan. With the data obtained it can be concluded that the use of carrageenan S. filiformis derived by sporulation natural cultivation is capable of forming gels when compared to stronger ι-carrageenan commercial could generate savings through the use of lower concentrations of the carrageenan commercial, to obtain the desired firmness of a product.